ADEA‐ADEE Shaping the Future of Dental Education III: The impact of scientific technologies and discoveries on oral health globally. Issue 1 (24th January 2020) - Dragan, Irina F.; Walji, Muhammad; Vervoorn, Marjoke; Quinn, Barry; Johnson, Lynn; Davis, Joan; Garcia, Lily T.; Valachovic, Richard W.
Abstract: The central purpose of scientific research and emerging dental health technologies is to improve care for patients and achieve health equity. The Impact of Scientific Technologies and Discoveries on Oral Health Globally workshop conducted joint American Dental Education Association (ADEA) and the Association for Dental Education in Europe (ADEE) 2019 conference, Shaping the Future of Dental Education III, highlighted innovative technologies and scientific discoveries to support personalized dental care in an academic and clinical setting. The 2019 workshop built upon the new ideas and way forward identified in the 2017 ADEE‐ADEA joint American Dental Education Association (ADEA) and the Association for Dental Education in Europe (ADEE) 2019 conference, Shaping the Future of Dental Education II held in London. During the most recent workshop the approach was to explore the "Teaching Clinic of the Future ". Participants applied ideas proposed by keynote speakers, Dr. Walji and Dr. Vervoorn to educational models (Logic Model) in an ideal dental education setting. It is only through this continuous improvement of our use of scientific and technological advances that dental education will be able to convey to students the cognitive skills required to continually adapt to the changes that will affect them and consequently their patients throughout their career. This workshop was a valuable experience for highlighting opportunities and challenges for all stakeholders when aiming to incorporate new technologies to facilitate patient care and students' education.